Kinetic Analysis of Monomolecular Cracking of Normal Alkanes (C4–C6) over Brønsted Acid Site of Zeolitic Type Catalyst with Energetic Evaluation of Transition States Using Quantum-Chemical Modeling; Russian Journal of Applied Chemistry; Vol. 98, iss. 5 - Forutan K. S. Kazvini Saba (2025, 2025)
Title screen